واقع استخدام تكنولوجيا المعلومات بالمؤسسة الاقتصادية الجزائرية دراسة حالة: مؤسسة صناعة الكوابل ENICAB ببسكرة ( من سنة 1988-2013) - نور الدين, أحمد قايد; إلهام, أ/ بروبة (Sciences humaines; Vol. 39 (2015): SCIENCES HUMAINES (Mars), 2015)
تهدف هذه الدراسة إلى إبراز واقع استخدام تكنولوجيا المعلومات بمؤسسة صناعة الكوابل ENICAB  ببسكرة، حيث أن استخدام تكنولوجيا المعلومات أدى إلى تعدد البرامج المؤتممة في الأسواق وبالتالي إعداد دفاتر الكترونية متعددة ومتنوعة تتناسب مع طبيعة وحجم المؤسسة، مما أدى إلى سهولة التعامل مع هذه الدفاتر بسرعة فائقة جدا في المراحل المختلفة عند التسجيل أو التعديل أو الإلغاء للبيانات،   ونتيجة هذا التطور المتسارع في تكنولوجيا المعلومات فقد نتج عنها أنماط وأساليب مختلفة في طرق إنجاز الأعمال بشكل مختلف وهذا ما سنحاول التطرق له في هذه الدراسة This study aims to highlight the reality of the use of information technology institution cabling industry ENICAB Bbiskrh, where the use of information technology has led to a multiplicity of  programs Almatmma in the  market and thus prepare the books of electronic multiple and varied commensurate with the nature and size of the organization, which led to the ease of dealing with these notebooks at very high speeds at different stages when registering or the modification or cancellation of the data, and as a result of this rapid development in information technology has resulted in patterns and styles in different ways of doing business differently and that's what we'll try to address it in this study.